Cardiopulmonary exercise testing in COVID-19 patients at 3 months follow-up. (1st October 2021) - Clavario, Piero; De Marzo, Vincenzo; Lotti, Roberta; Barbara, Cristina; Porcile, Annalisa; Russo, Carmelo; Beccaria, Federica; Bonavia, Marco; Bottaro, Luigi Carlo; Caltabellotta, Marta; Chioni, Flavia; Santangelo, Monica; et al.
Abstract: Background: Long-term effects of Coronavirus Disease of 2019 (COVID-19) are of utmost relevance. We aimed to determine: 1) the functional capacity of COVID-19 survivors by cardiopulmonary exercise testing (CPET); 2) the characteristics associated with cardiopulmonary exercise testing (CPET) performance; 3) the safety and tolerability of CPET. Methods: We prospectively enrolled consecutive patients with laboratory-confirmed COVID-19 from Azienda Sanitaria Locale 3, Genoa. Three months after hospital discharge a complete clinical evaluation, trans-thoracic echocardiography, CPET, pulmonary function tests, and dominant leg extension (DLE) maximal strength measurement were performed. Results: From the 225 patients discharged alive from March to November 2020, we excluded 12 incomplete/missing cases and 13 unable to perform CPET, leading to a final cohort of 200. Median percent-predicted peak oxygen uptake (%pVO2) was 88% (78.3–103.1). Ninety-nine (49.5%) patients had %pVO2 below, whereas 101 (50.5%) above the 85% predicted value. Among the 99 patients with reduced %pVO2, 61 (61%) had a normal anaerobic threshold: of these, 9(14.8%) had respiratory, 21(34.4%) cardiac, and 31(50.8%) non-cardiopulmonary reasons for exercise limitation. Inerestingly, 80% of patients experienced at least one disabling symtpom, not related to %pVO2 or functional capacity. Multivariate linear regression showed percent-predicted forced expiratory volume in one-second(β = 5.29, p  = 0.023), percent-predicted diffusing capacity of lungs for carbon monoxide(β = 6.31, p  = 0.001), and DLE maximal strength(β = 14.09, p  = 0.008) to be independently associated with pVO2. No adverse event was reported during or after CPET, and no involved health professional developed COVID-19. Conclusions: At three months after discharge, about 1/3rd of COVID-19 survivors show functional limitations, mainly explained by muscular impairment, calling for future research to identify patients at higher risk of long-term effects that may benefit from careful surveillance and targeted rehabilitation. Highlights: Long-term effects of COVID-19 are of utmost relevance. At 3 months half of COVID-19 patients previously discharged home have significant reduction in peak oxygen consumption at cardiopulmonary exercise test. One third of them has no cardio-pulmonary cause as the principal mechanism of CPET impairment. Four out of five experience at least one disabling symptom at 3-month evaluation. Symptoms are not related with abnormal peak oxygen consumption or functional capacity.